Giant Prolactinoma of Young Onset: A Clue to Diagnosis of MEN-1 Syndrome - Chandrika Jayakanthi Subasinghe; Noel Somasundaram; Pathmanathan Sivatharshya; Lalana Devi Ranasinghe; Márta Korbonits (Case Reports in Endocrinology)
Multiple endocrine neoplasia (MEN) type 1 syndrome is an autosomal dominant disorder caused by germline mutations in MEN1 gene, characterized by tumours in endocrine and nonendocrine organs. Giant prolactinoma is defined as tumours larger than 40mm with very high prolactin secretion. We report two unrelated Sri Lankan patients (8-year-old boy and a 20-year-old female) who presented with giant prolactinomas with mass effects of the tumours. The female patient showed complete response to medical therapy, while the boy developed recurrent resistant prolactinoma needing surgery and radiotherapy. During follow-up, both developed pancreatic neuroendocrine tumours. Genetic analysis revealed that one was heterozygous for a nonsense mutation and other for missense mutation in MEN1 gene. Screening confirmed familial MEN-1 syndrome in their families. High clinical suspicion upon unusual clinical presentation prompted genetic evaluation in these patients and detection of MEN1 gene mutation. Pituitary adenomas in children with MEN-1 syndrome are larger tumours with higher rates of treatment resistance. This report emphasizes importance of screening young patients with giant prolactinoma for MEN-1 syndrome and arranging long-term follow-up for them expecting variable treatment outcomes. Sri Lanka requires further studies to describe the genotypic-phenotypic variability of MEN-1 syndrome in this population.